Achieving Strong Teamwork Practices in Hospital Labor and Delivery Units - Farley, Donna O. (RAND Corporation, 2010)
To learn how hospital labor and delivery units can achieve effective and sustainable teamwork practices and how much such practices affect staff experiences and patient outcomes, RAND researchers studied five units as they implemented improvements in their teamwork practices over a one-year period. They identified some key factors required by any given strategy for teamwork improvement but no standard template for implementation.